Ant Species Diversity in the Establishing Area for Advanced Technology Institute at Lai-Nan Sub-district, Wiang Sa District, Nan Province, Thailand - SITTHICHAROENCHA, DUANGKHAE I; CHANTARASAWAT, NARATIP (Tropical Natural History, 2006)
The research is to investigate ant species composition and to study surface ground ant species structure using pitfall traps in three habitat types; deciduous dipterocarp forest, mango plantation, and grassland in the establishing area for the Advanced Technology Institute in Nan Province. Forty-six species of ants found in the study area belonging to 5 subfamilies; Formicinae, Ponerinae, Dolichoderinae, Pseudomyrmecinae, and Myrmicinae. The dominant species found in this area were Odontoponera denticulata and weaver ants Oecophylla smaragdina. Among the three types of habitats studied, the similarity index between deciduous dipterocarp forest and mango plantation was highest indicating the similarity in tree structures and microhabitats. The indices of dominance of deciduous dipterocarp forest and grassland indicate that dominance of ant species occurring in these areas. Some urban ant pests such as the yellow crazy ant Anoplolepis gracilipes, the ghost ant Tapinoma melanocephalum, and the pharaoh ant Monomorium pharaonis including the carpenter ants Camponotus spp. were found scattering around the study area. The awareness of these urban pests should be considered in the land-use plan for academic building construction.